2002
DOI: 10.1056/nejmoa021445
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of the Risk of Myocardial Infarction from Polymorphisms in Candidate Genes

Abstract: Determination of the genotypes of the connexin 37, plasminogen-activator inhibitor type 1, and stromelysin-1 genes may prove reliable in predicting the genetic risk of myocardial infarction and might thus contribute to the primary prevention of this condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
186
3
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 582 publications
(198 citation statements)
references
References 20 publications
7
186
3
2
Order By: Relevance
“…[4][5][6][7][8] Recently, genetic risk scores (GRSs) for CAD, consisting of specific genetic variants identified from genome-wide association studies, have also been associated with incident cardiovascular disease and have shown promise in improving cardiovascular risk prediction. [9][10][11][12][13][14][15][16][17][18][19][20][21][22] However, the exact predisposing mechanisms that account for the increased risk in patients with a FHx or a high GRS remain unclear.…”
mentioning
confidence: 99%
“…[4][5][6][7][8] Recently, genetic risk scores (GRSs) for CAD, consisting of specific genetic variants identified from genome-wide association studies, have also been associated with incident cardiovascular disease and have shown promise in improving cardiovascular risk prediction. [9][10][11][12][13][14][15][16][17][18][19][20][21][22] However, the exact predisposing mechanisms that account for the increased risk in patients with a FHx or a high GRS remain unclear.…”
mentioning
confidence: 99%
“…Recent genetic association studies link the thrombospondin (TSP) 2 protein family to the development of atherosclerotic lesions (3)(4)(5)(6)(7)(8)(9)(10). TSP-1 was found in early atherosclerotic lesions (11), in injured vascular walls (12,13), and in cardiac allografts where its expression correlated with the degree of vasculopathy (14).…”
mentioning
confidence: 99%
“…The TSP-1 SNP is a rare N700S recessive trait (1% frequency) but has the highest association with disease (odds ratio for MI ϭ 8.66). This rarity leads to a low likelihood of successful replication in small studies (7,8), but in one subsequent preliminary report (9) this disease association of the Ser-700 variant was corroborated.…”
mentioning
confidence: 99%